As transformações da relação museu e público: a influência das tecnologias da informação e comunicação no desenvolvimento de um público virtual - (:unkn) unknown (Universidade Federal do Rio de Janeiro / Instituto Brasileiro de Informação em Ciência e Tecnologia, 2005)
Analysis of the transformations in the museum and visitors relation, considering the issues related to museums evolution, the new information and communication technologies and museums as information systems. Studies of the electronic communication and information networks, measuring how much the Internet/Web contributes to the formation of a virtual public and to the expansion of museum attendance in loco to exhibitions and to other museum,information sectors, in an integrated manner. The methodology comprises the Museu Histórico Nacional in Rio de Janeiro as study setting, the theoretical frame is based on Information Science, Museology and Communication authors; and the empirical research is developed in two sections: the analysis of the electronic messages of Museu Histórico Nacional virtual visitors in order to design visitors profile and main demands for information; knowledge of visitors behavior and the relation between physical and virtual museum attendances, based on interviews through the Internet. As a product of this research and based on its results, is designed a proposal of Museology and Museums Portal (Website) to be implemented in the country
Keywords: Museu e público; Tecnologias de informação e comunicação; Público virtual; Museu; CNPQ::CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO